Organic geochemical characteristics and source determination of shale oil in Dongying Sag： A case study of Es4U in Niuxie 55 Block of Niuzhuang Subsag - WANG Xiuhong; CHEN Tao; ZHANG Shouchun; LI Zheng; NIU Zicheng; WANG Xin (Youqi dizhi yu caishoulu)
The precise determination of shale oil sources is of great significance for the evaluation of sweet spots and resource potential in shale oil. Exploration practice indicates significant differences in the biomarker fingerprint characteristics of shale oil of the Upper Submember of the 4th Member of the Eocene Shahejie Formation （Es4U） from some wells in Niuzhuang Subsag in Dongying Sag， reflecting that shale oil accumulation might not be the traditional understanding of “self-generation and self-storage.” In order to meet the needs of fine exploration， it is urgent to explore the differences in hydrocarbon generation in each layer series and the main hydrocarbon supply layer series. Geochemical testing techniques， such as light hydrocarbon and gas chromatography-mass spectrometry， etc.， were comprehensively used， and a systematic study was conducted on the organic geochemical characteristics of hydrocarbon source rocks and shale oil from key wells in the Upper Submember of the 4th Member of the Eocene Shahejie Formation （Es4UC） in Niuxie 55 Block of Dongying Sag. Then， the oil sources were finely determined. The results indicate that the organic matter development characteristics of each layer series of Es4UC in Niuxie 55 Block have heterogeneity， reflecting vertical changes in organic matter sources and thermal evolution. At the same time， the distinct differences in hydrocarbon generation characteristics of each layer series are caused by periodic changes in factors， such as organic matter sources and sedimentary environments， etc. A fine oil source correlation shows that the shale oil from Well NY1-AHF and Well NY1-BHF in this block， respectively， come from the shale of the third and fourth layer series of Es4UC， reflecting the source control characteristics of differential shale oil aggregation. Comprehensive analysis suggests that fine exploration and deployment of shale oil should pay attention to the main hydrocarbon supply layer series and consider certain macroscopic structural backgrounds. Exploring high-quality reservoir space， especially effective fault transport areas， is an essential sweet spot element for achieving the efficient development of shale oil in advantageous source rock development areas.